2016
DOI: 10.1021/acs.analchem.5b04830
|View full text |Cite
|
Sign up to set email alerts
|

Dopant-Assisted Positive Photoionization Ion Mobility Spectrometry Coupled with Time-Resolved Thermal Desorption for On-Site Detection of Triacetone Triperoxide and Hexamethylene Trioxide Diamine in Complex Matrices

Abstract: Peroxide explosives, such as triacetone triperoxide (TATP) and hexamethylene trioxide diamine (HMTD), were often used in the terrorist attacks due to their easy synthesis from readily starting materials. Therefore, an on-site detection method for TATP and HMTD is urgently needed. Herein, we developed a stand-alone dopant-assisted positive photoionization ion mobility spectrometry (DAPP-IMS) coupled with time-resolved thermal desorption introduction for rapid and sensitive detection of TATP and HMTD in complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…However, as depicted in Fig. 2, the ion peaks of dursban (K 0 ¼ 1.18 cm 2 V À1 s À1 ) and malathion (K 0 ¼ 1.17 cm 2 V À1 s À1 ) fully overlapped, and the peaks of when the applied high voltage was positive, the reactant ions (Ac) 2 H + (H 2 O) n were produced via the photoionization of the acetone dopant, 26 and then the OPP molecules were ionized by proton transfer reactions with (Ac) 2 H + (H 2 O) n , as described in reactions (1) and (2). (H 2 O) n , as described in reaction (4).…”
Section: Overlapping Ion Peaks Of Oppsmentioning
confidence: 97%
“…However, as depicted in Fig. 2, the ion peaks of dursban (K 0 ¼ 1.18 cm 2 V À1 s À1 ) and malathion (K 0 ¼ 1.17 cm 2 V À1 s À1 ) fully overlapped, and the peaks of when the applied high voltage was positive, the reactant ions (Ac) 2 H + (H 2 O) n were produced via the photoionization of the acetone dopant, 26 and then the OPP molecules were ionized by proton transfer reactions with (Ac) 2 H + (H 2 O) n , as described in reactions (1) and (2). (H 2 O) n , as described in reaction (4).…”
Section: Overlapping Ion Peaks Of Oppsmentioning
confidence: 97%
“…In 1895, Wolffenstein found and synthesized triacetone triperoxide (TATP) [2], which is a self-made explosive synthesized from the common chemicals acetone (C 3 H 6 O) and hydrogen peroxide (H 2 O 2 ) found in daily life [3,4]. Because it is difficult to detect [5,6], it is more popular for terrorist activities [4,7,8,9,10]. Therefore, it is very important to carry out the continuous monitoring of TATP precursors (C 3 H 6 O and H 2 O 2 ) in public places [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…APPI has previously been applied to the analysis of explosive compounds, both in liquid samples and as trace vapors. For instance, Song et al used APPI to analyze a range of explosives in liquid samples by negative mode LC/MS; while Cheng et al and later Jiang et al demonstrated the detection of thermally desorbed explosive vapors using a custom‐built APPI‐IMS device, taking advantage of a basic time‐of‐flight ion mobility design. Their custom‐built APPI sources did not include an extended field‐free reaction region; however, they were able to demonstrate detection limits in the mid‐ to high‐picogram range for a variety of common explosive residues.…”
Section: Introductionmentioning
confidence: 99%